1986
DOI: 10.1159/000249262
|View full text |Cite
|
Sign up to set email alerts
|

Captopril-Induced Lichen planus pemphigoides with Pemphigus-Like Features

Abstract: We report a case of a bullous lichenoid eruption due to the intake of captopril. Clinical, histological, direct immunofluorescence and ultrastructural features were consistent with the diagnosis of lichen planus pemphigoides. In addition, the in vivo immunological study also revealed an intercellular fluorescence, similar to that seen in pemphigus. Complex drug-induced cutaneous reactions have been previously reported with other drugs, especially with D-penicillamine, which bears chemical similarities with cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 19 publications
0
11
1
3
Order By: Relevance
“…Direct immunofluorescence (DIF) reveals linear deposits of IgG and/or C3 along the basement membrane zone (BMZ). Although LPP is usually idiopathic, hepatitis B, psoralen ultraviolet A therapy and various drugs, including ramipril, simvastatin, cinnarizine, captopril and furosemide, have been reported to be associated with LPP 1–7 . We present a case of LPP associated with Chinese herbs.…”
mentioning
confidence: 97%
“…Direct immunofluorescence (DIF) reveals linear deposits of IgG and/or C3 along the basement membrane zone (BMZ). Although LPP is usually idiopathic, hepatitis B, psoralen ultraviolet A therapy and various drugs, including ramipril, simvastatin, cinnarizine, captopril and furosemide, have been reported to be associated with LPP 1–7 . We present a case of LPP associated with Chinese herbs.…”
mentioning
confidence: 97%
“…Previous studies of the skin in such pa tients included direct immunofluorescence of bullous lesions [19] and the analysis of the lymphocytic subpopulations of the dermal infiltrate in 1 case of severe cutaneous reac tion [20], The clinical and histological fea tures in this late case were similar to those of mycosis fungoides, and the immunohistological study found a T helper type infiltrate associated with an increase in Langerhans cells. According to the authors, B lympho cyte stimulation by the T helper population may account for the frequency of circulating antibodies in captopril-treated patients [20].…”
Section: Discussionmentioning
confidence: 64%
“…Şu ana kadar tanımlanan olgularda genellikle önce likenoid lezyonların oluştuğu sonra bül gelişiminin klinik tabloya eklendiği bildirilmiş olsa da, bül oluşumunun likenoid lezyonlardan önce gözlendiği ya da bizim olgumuzda olduğu gibi likenoid papüller ve vezikülobüllöz lezyonların eşzamanlı başladığı olgular da bildirilmiştir [1][2][3][4] . Bizim olgumuzda gözlenmese de, bazı olgularda oral mukozada retiküler beyaz plakların ve yüzeyel ülserasyon alanlarının görüldüğünden de bahsedilmiştir 13,14,16 . Klinik, histopatolojik ve immünolojik olarak LP ve büllöz pemfigoidin karışımı olarak karşımıza çıkan LPP'nin ayrı bir immünolojik antite mi yoksa basit bir LP ve büllöz pemfigoid birlikteliği mi olduğu tartışmalıdır.…”
Section: Discussionunclassified
“…Olgumuzda indirekt immünofloresan ve immünoblotting incelemeler yapılamamış olmasına rağmen klinik, histopatolojik ve direkt immünofloresan bulgular LPP ile uyumludur. Genellikle idiyopatik olmakla birlikte literatürde hepatit B virüsü infeksiyonu, maliniteler, dar band UVB, PUVA ve bazı ilaçlarla ilişkili olarak ortaya çıkan LPP olguları bildirilmiştir [5][6][7][8][9][10][11][12][13][14][15][16] . LPP oluşumunda suçlanan ilaçlar arasında sinnarizin, ramipril, kaptopril, simvastatin, furusemid, parasetamol, ibuprofen ve paroksetin bulunmaktadır [7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionunclassified
See 1 more Smart Citation